ANALISIS RESTRUKTURISASI PEMBIAYAAN MURABAHAH BERMASALAH AKIBAT PANDEMI COVID-19 DI BPRS MUSTAQIM BANDA ACEH - Asnul, Aska; Bustamam, Bustamam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
Restructuring financing is one of the policies that can be implemented to overcome problematic financing that frequently arises in financial institutions, including murabahah financing. This study aims to assess the conformity of the implementation of the applicable regulations and to identify the various types of restructuring implementation in the settlement of troubled murabahah financing at BPRS Mustaqim Banda Aceh resulting from the Covid-19 pandemic. This study employed a descriptive-qualitative methodology with BPRS Mustaqim Banda Aceh as the subject of study. Interviews and document reviews were conducted to collect research data. The findings of this study indicate that the restructuring implemented by BPRS Mustaqim Banda Aceh conforms to the DSN-MUI Fatwa and SE BI and that the implementation of restructuring in dealing with troubled murabahah financing due to the Covid-19 pandemic includes rescheduling, reconditioning, and restructuring by DSN-MUI Fatwa Number 49/DSN-MUI/II/2005 and PBI Number 10/18/PBI/2008.